2019
DOI: 10.1590/0034-737x201966050005
|View full text |Cite
|
Sign up to set email alerts
|

Shoot proliferation, leaf anatomy and pigment content of Eugenia dysenterica growing in conventional and natural ventilation systems

Abstract: Shoot proliferation, leaf anatomy and pigment content of Eugenia dysenterica growing in conventional and natural ventilation systems 1 Natural ventilation micropropagation systems differ from conventional systems by allowing gas exchange between the internal and external media of the culture flask. The objective of this work was to compare the conventional system of in vitro propagation of Eugenia dysenterica (Mart.) DC. with a natural ventilation system. For shooting, explants were inoculated into test tubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Gas exchange in micropropagation has been shown to be an effective means of improving plantlet quality. Silveira et al (2019) observed that natural ventilation resulted in increases of 448.53% in the number of leaves, 85.64% in chlorophyll a content and 74.90% in chlorophyll b content in micropropagated Eugenia dysenterica DC. (Myrthaceae).…”
Section: In Vitro Growthmentioning
confidence: 99%
“…Gas exchange in micropropagation has been shown to be an effective means of improving plantlet quality. Silveira et al (2019) observed that natural ventilation resulted in increases of 448.53% in the number of leaves, 85.64% in chlorophyll a content and 74.90% in chlorophyll b content in micropropagated Eugenia dysenterica DC. (Myrthaceae).…”
Section: In Vitro Growthmentioning
confidence: 99%